A Joint Construction Practice in an Academic Writing Course in an Indonesian University Context - Aunurrahman Aunurrahman; Fuad Abdul Hamied; Emi Emilia (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
This research aims to explore the students’ writing and critical thinking capacity in a joint construction practice in an academic writing course. The course applied a genre-based approach in teaching academic writing and critical thinking to first-year English as a Foreign Language students of a private university in Pontianak, West Kalimantan, Indonesia. A combination of explicit teaching, group discussion, and online review sessions was employed in the joint construction practice for three meetings. The source for the data collection was a jointly constructed text. The text was selected from thirty-six students who worked in groups. Every group consisted of low achievers, medium achievers, and high achievers in writing. The text was analyzed using functional grammar. The analysis shows that the students had gained a good control of the exposition genre with its linguistic features. Thematic progression and logical connectors at the text level and circumstances (adverbs) at the clause level had realized critical thinking skills and dispositions. Several grammatical mistakes and improper lexical choices were identified but did not interfere with the purpose of the text. The findings suggest that having more classroom meetings will make explicit teaching and group discussion work effectively before the students begin to write independently. Moreover, online review sessions can support the students' learning but with limitations.